Effect of pre-oxidation on hot corrosion resistance of HR3C stainless steel in sulfate salt with or without Fe2O3. (November 2021) - Yu, Zheng; Lu, Jintao; Chen, Minghui; Wang, Jinlong; Wang, Fuhui
Abstract: HR3C steel exhibits high oxidation resistance in air at 700 °C owing to the formation of a dense chromia scale. In the presence of sulfate salt deposition (Na2 SO4 :K2 SO4 = 1:1), hot corrosion occurs. It leads to the dissolution and re-precipitation of Cr2 O3 platelets and severe internal corrosion. Pre-oxidation can notably enhance corrosion resistance with almost no internal corrosion zone. When the deposited sulfate salt contains Fe2 O3 (Na2 SO4 :K2 SO4 :Fe2 O3 = 1:1:1), HR3C steel suffers even severer hot corrosion. Its scale spalls off easily and internal corrosion develops deep into the steel. Meanwhile, pre-oxidation played almost no positive effect on corrosion in sulfate salt containing Fe2 O3 . Highlights: HR3C steel exhibits high oxidation resistance in air at 700 °C. Sulfate salt deposition leads to hot corrosion, including the formation of Cr2 O3 platelets and severe internal corrosion. Pre-oxidation enhances corrosion resistance with almost no internal corrosion. When the sulfate salt contains Fe2 O3, the steel suffers even severer hot corrosion. Pre-oxidation plays no positive effect on corrosion in sulfate salt containing Fe2 O3 .